Biochar for Sustainable Restoration of Heavy Metals Contaminated Soil: Performance, Assessment, and Mechanisms - Rehman, Hamid; Khan, Aqib Hassan Ali; Rehman, Wasif Ur; Ahmad, Mahtab; Iqbal, Mazhar (WILEY-V C H VERLAG GMBH, 2025)
Soil degradation, driven by anthropogenic activities, has led to heavy metal pollution. These heavy metals harm the soil structure, physiology, and biota. It is examined how biochar influences the structure, hydrology, microbiological activity, and enzyme function in heavy-metal-contaminated soils. Key factors include soil type, biochar composition, metal immobilization effectiveness, and the mechanisms involved, such as sorption, desorption, and redox reactions in contaminated soil. Biochar offers sustainable advantages for heavy metal immobilization, though its efficacy depends on soil characteristics like pH and physiochemical and biological properties. Further, sorption/desorption and redox reactions have been playing a vital role in governing the immobilization of heavy metals within soils. Collectively, the findings indicate that biochar provides an effective and sustainable solution for the restoration of heavy-metal-contaminated soils by enhancing metal immobilization and protecting soil ecosystems. This review provides insights into cost-effective, and ecofriendly biochar-based optimization for soil recoveries. This review synthesizes current evidence on biochar's efficacy, cost-efficiency, and environmental performance in improving soil health and agricultural productivity. Moreover, this review highlights the potential of biochar and bacteria-based strategies for enhancing soil health and agricultural productivity while providing insights into optimizing remediation processes for site-specific conditions.
Keywords: biochar; bioremediation; heavy metals; plant microorganism interactions; soil; POLYCYCLIC AROMATIC-HYDROCARBONS; MICROBIAL COMMUNITY STRUCTURE; POTENTIALLY TOXIC ELEMENTS; ZERO-VALENT IRON; PYROLYSIS TEMPERATURE; HEXAVALENT CHROMIUM; ACTIVATED CARBON; AQUEOUS-SOLUTION; CADMIUM REMOVAL; ORGANIC-MATTER; Science & Technology - Other Topics; Materials Science